Positive Mathematical Programming to Model Regional or Basin-Wide Implications of Producer Adoption of Practices Emerging from Plot-Based Research - Nicolas Quintana-Ashwell (MDPI AG, 2021)
A method for calibrating models of agricultural production and resource use for policy analysis is proposed to leverage multidisciplinary agricultural research at the National Center for Alluvial Aquifer Research (NCAAR). An illustrative example for Sunflower County, MS, is presented to show how plot-level research can be extended to draw systemic region or basin wide implications. A hypothetical improvement in yields for dryland soybean varieties is incorporated into the model and shown to have a positive impact on aquifer outcomes and producer profits. The example illustrates that a change in one practice-crop combination can have system-wide impacts, as evidenced by the change in acreages for all crops and practices.